Pulmonary rehabilitation in long COVID: more than just natural recovery!?. Issue 3 (31st August 2021) - Gloeckl, Rainer; Leitl, Daniela; Jarosch, Inga; Schneeberger, Tessa; Nell, Christoph; Stenzel, Nikola; Daher, Ayham; Dreher, Michael; Vogelmeier, Claus F.; Kenn, Klaus; Koczulla, Andreas R.
We thank A. Hussain and co-workers for their correspondence regarding our study on the benefits of pulmonary rehabilitation (PR) in coronavirus disease 2019 (COVID-19) [1]. In the light of missing randomised controlled trials, some arguments suggest that pulmonary rehabilitation has beneficial effects beyond natural recovery https://bit.ly/3ze2xvw